1997
DOI: 10.2527/1997.75102684x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A repletion in thoroughbred mares with retinyl palmitate or beta-carotene.

Abstract: Forty-five Thoroughbred mares used in an 8-mo depletion study were kept for an additional 20 mo on the same three forage diets (15 mares each): 2-yr-old orchardgrass hay and vitamin A-free concentrate on a drylot (HC); pasture, orchardgrass/alfalfa hay, and vitamin A-free concentrate (PHC); or pasture and orchardgrass/alfalfa hay only (PH). Each diet group was divided into three subgroups, and mares (n = 5) in each group were given either retinyl palmitate (A) at twice the NRC (1989) recommended daily intake, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 0 publications
0
9
2
2
Order By: Relevance
“…These findings are in contrast with those reported by Schweigert and Gottwald (1999), who observed that the concentrations of β-carotene in the milk of mares are comparable with those of cows. Greiwe-Crandell et al (1997) hypothesized that the bioavailability of β-carotene may be overestimated because of the presence or absence of other substances in the diet that may influence efficiency of absorption and metabolism, and there are significant differences in β-carotene utilization within species, which could explain the differences found in the present study. Moreover, Schweigert and Gottwald (1999) established that β-carotene levels in milk at all stages of lactation are highly dependent on the levels in plasma; however, we did not observe significant correlations (P > 0.05) in this sense neither in mares nor in cows.…”
Section: Resultscontrasting
confidence: 43%
See 1 more Smart Citation
“…These findings are in contrast with those reported by Schweigert and Gottwald (1999), who observed that the concentrations of β-carotene in the milk of mares are comparable with those of cows. Greiwe-Crandell et al (1997) hypothesized that the bioavailability of β-carotene may be overestimated because of the presence or absence of other substances in the diet that may influence efficiency of absorption and metabolism, and there are significant differences in β-carotene utilization within species, which could explain the differences found in the present study. Moreover, Schweigert and Gottwald (1999) established that β-carotene levels in milk at all stages of lactation are highly dependent on the levels in plasma; however, we did not observe significant correlations (P > 0.05) in this sense neither in mares nor in cows.…”
Section: Resultscontrasting
confidence: 43%
“…No significant differences in retinol levels were observed between both species. Previously, Greiwe-Crandell et al (1997) reported that grazing horses derive vitamin A from provitamin-A carotenoids present in the forages, but the efficiency of this conversion is relatively poor in these animals. Furthermore, it has been stated (Martin et al, 2004) that the levels of vitamin A in blood of cows was unaffected by the diet because of the animal's metabolic regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Greiwe-Crandell et al [151] supplemented VA-depleted horses with 215 mg of BC in synthetic beadlet form daily for 4 weeks and found that VA status, measured by serum retinol and a relative dose-response test, was not improved as compared to controls and horses supplemented with 22 mg retinyl palmitate. The retinyl palmitate dose was twice that recommended by the NRC.…”
Section: Species Differences In β-Carotene Metabolismmentioning
confidence: 99%
“…Os eqüinos dependem do alimento como única fonte de vitamina A (Izaguirre e Miyasaka, 2001) e, segundo Greiwe-Crandell et al (1997), a eficiência de conversão do betacaroteno em vitamina A é, relativamente, pequena na espécie eqüina. A conversão de betacaroteno em retinol na mucosa intestinal diminui proporcionalmente ao aumento das concentrações dessa pró-vitamina na dieta e pode variar de acordo com a espécie de forrageira ingerida pelos animais (Nutrient..., 1989).…”
Section: Introductionunclassified
“…Para Blakley e Bell (1994), a suplementação com vitamina A, provavelmente, não é requerida por eqüinos que recebem forragens frescas ou são mantidos a pasto. Éguas mantidas em pastagens no inverno não apresentaram queda no status de vitamina A como as que permaneceram em cocheiras, ressaltando que a forma natural do betacaroteno nas pastagens, solúvel em óleo, facilita absorção intestinal (Greiwe-Crandell et al, 1997). De acordo com o National Research Council (Nutrient..., 1989), a suplementação com betacaroteno não é necessária em éguas mantidas a pasto ou que estejam sendo alimentadas com forragens que apresentem altos teores de betacaroteno.…”
Section: Introductionunclassified